(untitled) - Beeson, Mark (New York, 2004)
Eleven international academics contribute 11 specially-commissioned chapters providing a multidimensional analysis of the economic, political, social, and strategic factors that have shaped Southeast Asia at the national and regional levels. Coverage includes the impacts of the colonial period and of the Cold War; historical factors influencing economic development; democratic reform; Asian values; organized labor; the role of Islam in regional affairs; security concerns; environmental challenges; interactions between Southeast Asia and the three most influential regional actors--the U.S., Japan, and China; and the historical development of regional cooperation
Keywords: Southeast Asia,National security,Southeast Asia; Economic conditions,Southeast Asia,Politics and government; 1945-